The effects of non-contributory pensions on material and subjective well being - Rosangela Bando Grana; Sebastián Galiani; Paul J. Gertler (Inter-American Development Bank (IDB), 2017)
Public expenditures on non-contributory pensions are equivalent to at least one percent of GDP in several countries in Latin America and is expected to increase. We explore the effect of non-contributory pensions on the well-being of the beneficiary population by studying the Pension 65 program in Peru, which uses a poverty eligibility threshold. We find that the program reduced the average score of beneficiaries on the Geriatric Depression Scale by nine percent and reduced the proportion of older adults doing paid work by four percentage points. Moreover, households with a beneficiary increased their level of consumption by 40 percent. All these effects are consistent with the findings of Galiani, Gertler and Bando (2016) in their study on a non-contributory pension scheme in Mexico. Thus, we conclude that the effects of non-contributory pensions on well-being in rural Mexico can be largely generalized to Peru.
Keywords: H4; H3; I1; I3; 330; Non-contributory pensions; poverty; mental health and well being